Anmeldelse af Parliaments and Coalitions. The Role of Legislative Institutions in Multiparty Governance - Jensen, Henrik (Politica, 2015)
Lanny W. Martin og Georg Vanberg, Parliaments and Coalitions. The Role of Legislative Institutions in Multiparty Governance. ECPR/Oxford University Press, 2011 (anmeldt af Henrik Jensen)